(untitled) - Riesman, David (New York, 1953)
Contents: The interpretation of Veblen offered by this book emphasizes above all the ambiguity, even the internal contradictions, of his thought. Inconsistency, as Emerson said, need not be altogether a defect: it may reflect a complex and honest mind working on inherently difficult problems
Keywords: Khoa học xã hội,Social sciences